Impact of Cost of Prescription Antibiotics on the Gross Domestic Product (GDP) of the Iraqi Population - Janabi, Ahmed Abdul Hussein S. AL; Janabi, Ali Abdul Hussein S. AL; Alkhalidi, Noor Salam (Anti-Infective Agents, 2026)
Introduction/ObjectiveThe cost of an antibiotic may significantly increase personal expenses, which affects a country's total gross domestic product (GDP). The percentage of lost GDP per person of the Iraqi population due to the cost of antibiotics was studied.MethodsA prescriptive study was conducted to assess the cost of common prescription antibiotics in Iraq based on data obtained from 32 pharmacies in four Iraqi governorates. The cost of antibiotics based on the total GDP of patients was determined as a percentage.Results and DiscussionThe specialization of physicians and the type and form of antibiotics were the effective factors associated with the impact of the cost of antibiotics on the GDP per person in Iraq. A high percentage of GDP per person was reduced by the cost of antibiotics prescribed by pediatricians and otolaryngologists (ENT) (64.18% and 56.19%, respectively). Cefpodoxime and ciprofloxacin were the costliest types of antibiotics with greater GDP reduction. Based on the form, syrups and tablets were the most expensive antibiotics. Amoxicillin had forms costing between 27.02% and 77.69% of the total GDP per patient, while chloramphenicol had only one form, drops.ConclusionThe cost of antibiotics has a major impact on the overall GDP of the population of Iraq. This effect is significantly influenced by the specialization of physicians, and the type and the form of antibiotic. Restricting the prescription of unnecessary antibiotics and expensive types is highly recommended to lower the cost and burden on the GDP of Iraqis.
Keywords: Antibiotics